Dependence of the concentrations of 137Cs and potassium in extracted soil solutions on soil humidity before centrifugation - V. V. Prorok; P. J. White; O. I. Dacenko; L. A. Bulavin; S. E. Zelensky; L. Yu. Melnychenko; S. G. Rozouvan; L. V. Poperenko (Ядерна фізика та енергетика)
Concentrations of 137Cs and potassium in solutions extracted by centrifugation from soils selected at some experimental sites in the 10-km Exclusion Zone of Chornobyl Nuclear Plant were determined. The results showed that for the majority of investigated soils, the concentration of 137Cs in soil solution depends on the humidity of the soil before centrifugation. It is possible to explain the dependence of the concentration of 137Cs in the soil solution on soil humidity from the dependence of the concentrations of molecules of different molecular-gravimetric fractions in soil solution on soil humidity. Considerable amount of 137Cs in soil solution is associated with these molecules, that is why the concentration of 137Cs in the extracted soil solution changes with the humidity of soil. These dependences differ between soils. For the majority of investigated soils the concentration of 137Cs in the extracted soil solution increases with increasing humidity of the soil. By contrast, soil humidity had no effect on the potassium concentration in the extracted soil solution for any soil investigated. It is concluded, that potassium is practically not associated with molecules of different molecular-gravimetric fractions in the extracted soil solutions.